Upaya Meningkatkan Partisipasi Dan Prestasi Belajar Peserta Didik pada Mata Pelajaran Pendidikan Pancasila Melalui Model Pembelajaran STAD Berbantuan Media Storyjumper di Kelas 4 SDN Gunungtelu 02 Kabupaten Cilacap - Agung Nugroho; Mutiara Anisa (CENDEKIAWAN, 2025)
The low academic achievement and participation of students in Pancasila Education in Grade 4 at SDN Gunungtelu 02 prompted the implementation of this classroom action research. This study aimed to address the lack of student engagement and academic performance by applying the Student Team Achievement Division (STAD) model assisted by Storyjumper media in Pancasila Education. The study was conducted in two cycles, with two sessions in each cycle, involving 16 fourth-grade students. Data were collected through documentation, observation sheets, assessment sheets, and questionnaires. The findings revealed a consistent improvement in student participation and academic achievement. In Cycle I, student participation reached 79.99% (categorized as good) and increased to 84.64% (still categorized as good) in Cycle II. The average score of student achievement in Cycle I was 78, with a mastery level of 65.65% (categorized as fair), which improved to an average score of 90 and a mastery level of 90.65% (categorized as good) in Cycle II. These results indicated that the success indicators were achieved. The use of the STAD strategy assisted by Storyjumper media positively impacts student participation and academic performance, thereby meeting the expected success criteria.